CONTROLLED INTERSYSTEM COMMUNICATION - Zaitsev D.A.; Tirshu M.; Golub I.V.; Gore N. (Problems of the Regional Energetics, 2010)
There are described results of researches regarding application of the new means for control of mode of electric power transmission and distribution on the basis of IPC (Interphase Power Controller) taking into account development of external connections of the Moldavian power supply system. The variant of application of classical IPC on base of High Voltage Line Beltsy-Suceava is considered. The management method by power flows in this section on the basis of application of PST (Phase Shift transformer), connected in parallel with IPC is offered and investigated and its technical efficiency is proved.